Iodine(III)-Mediated Oxidative Hydrolysis of Haloalkenes: Investigation of the Effect of Iodine(III) Reagents - Dagenais, Robin; Lauriers, Antoine Jobin-Des; Legault, Claude Y. (Synthesis, 2017)
The iodine(III)-mediated oxidative transposition of vinyl halides to the corresponding α-halo ketones has been recently reported. The method is high yielding and offers good substrate scope. The investigation of other iodine(III) reagents to promote this reaction is described. The newly developed protocol reduces the number of waste products formed in the synthetic transformation. A structure–reactivity relationship study of numerous [hydroxy(tosyloxy)iodo]arenes toward haloalkenes is reported. The results highlight the challenge of obtaining a chemoselective reaction using these reagents.
Keywords: hypervalence; iodine; oxidation; vinyl halides; chemoselectivity